KEMAMPUAN BACA AI-QURAN SIS WA SMP DIKABUPATEN GOWA - pat badrun (Al-Qalam, 2007)
This research was conducted in Gowa, South Sulawesi. Especially atSMPN 1 Sungguminasa, SMPN 3 Sungguminasa, and SMPN 4Sungguminasa. This research aims to describe the student ability onreading Al-Qur'an and factors influence that ability. This uses quantitativemethod, where data was collected by questioner. Then, data wasanalyzed by statistical analysis.This research indicates that ability degree on reading Al-Qur'an ofthose students of the three schools is commonly good enough. Thisgood ability was influenced by several factors, are (a) local traditionassumes that ability on reading the Al-Qur'an is an obligatory;(b) theapplication of government regulation no. 07/2003 about "free fromQuranic script less ", especially to all elementary and junior high schoolstudents; (c) the school regulation that makes the student prepare themselveson reading Al-Qur'an. This good ability, than, influenced by prejuniorhighschool education, method in reading and writing Al-Qur'an,and the student motivation.